Flexible mass spring method for modelling soft tissue deformation - Omar, Nadzeri; Zhong, Yongmin (Penerbit Universiti Malaysia Pahang, 2021)
It is well accepted that soft tissue deformation is a combination of linear and nonlinear response. During small displacements, soft tissues deform linearly while during large displacements, soft tissues show nonlinear deformation. This paper presents a new approach for modelling of soft tissue deformation, from the standpoint of Mass Spring Method (MSM). The proposed MSM model is developed using conical spring methodology which allow the MSM model to have different stiffnesses at different displacements during deformation. The stiffness variation creates flexibility in the model to simulate any linear and nonlinear deformations. Experimental results demonstrate that the deformations by the proposed method are in good agreement with those real and phantom soft tissue deformations. Isotropic and anisotropic deformations can be accommodated by the proposed methodology via conical spring geometry and configuration of the springs. The proposed model also able to simulate typical viscoelastic behaviour of soft tissue.